Persistence of profit in the banking sector: Literature synthesis and new avenues for research - Meknassi, Siham; ADEL, Nabil (Revue Internationale des Sciences de Gestion, 2021)
The persistence of profit continues to generate significant interest in empirical micro econometrics. Today two explanatory paradigms are used by researchers, namely the static and dynamic hypotheses of the competitive environment. The first paradigm attributes the persistence of profit by the industry characteristics (intensity of competition and barriers to entry). In contrast, the second explains it by the companies’ strategies (innovation and reduction of production costs). While researchers widely use these explanatory paradigms, they do not fully establish conditions for profit to form and persist. This article presents the state of the art of literature on profit persistence in the banking industry and mobilizes two additional explanatory paradigms. The first paradigm (agency theory) deals with integrated groups where the shareholder is the owner and a contributor to business and, therefore, to profit. The second one (dynamic nonlinear systems theory) explains the interactions between the static and the dynamic hypothesis of the competitive environment leading to the formation and persistence of profit. We complete this conceptual framework with a review of the measurement of profit and the determinants of its persistence, as they emerge from empirical observations.